Sodium-ion positive electrode material with low residual alkali content and preparation method thereof

CN116613294BActive Publication Date: 2026-10-27WANHUA CHEM GRP BATTERY TECH CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310749621.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2026-10-27
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

[0003]O3型的层状氧化物的钠离子正极材料具有高的放电比容量,然而层状氧化物的钠离子正极材料空气稳定性差,残碱高,制备电池时加工困难,极大的限制了钠离子电池的应用,因此提高钠离子正极材料的稳定性至关重要

Benefits of technology

[0033]本发明研究发现:XRD晶体结构中I(006)/I(101)和FWHM(006)/FWHM(101)在合适的范围内,钠层间距适当,有利于钠离子的脱出,容量高;I(113)/I(018)和FWHM(113)/FWHM(018)在合适的范围内,在循环过程中能有效抑制不可逆相变的发生,得到的钠离子电池材料结构更加稳定,残碱含量更低;本发明通过优选2种不同粒径的前驱体分别和钠源烧结,通过调整不同粒径的前驱体最佳的钠配比和烧结温度,有利于得到得到本发明的特定的晶体结构;通过金属层和钠层金属元素的共同掺杂,以及铝、磷酸盐的包覆,使其有利于得到合适的I(006)/I(101)值和FWHM(006)/FWHM(101)值,提高了钠层的稳定性,阻止了与电解液的副反应和金属离子的溶出,制备了稳定低残碱含量的钠离子正极材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116613294B_ABST
    Figure CN116613294B_ABST
Patent Text Reader

Abstract

The application provides a sodium-ion positive electrode material with low residual alkali content and a preparation method thereof, and the structure of the sodium-ion positive electrode material is Na x Ni y Fe z Cu a Mn b M 1‑y‑z‑a‑b O2, wherein 0.70≤x≤1.20, 0 The ratio of I(113) / I(018) in the XRD crystal structure of the sodium-ion positive electrode material is between 0.7-1.2, and the ratio of FWHM(113) / FWHM(018) is between 1.2-1.8; the ratio of I(006) / I(101) is between 0.6-1.3, and the ratio of FWHM(006) / FWHM(101) is between 1.0-1.5. The prepared sodium-ion battery positive electrode material has excellent air stability, low residual alkali, stable processing performance and excellent electrochemical performance, and can be used to prepare an electric core in a humidity range of 10-30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium battery technology, specifically relating to a sodium-ion cathode material with low residual alkali content and its preparation method. Background Technology

[0002] Lithium-ion batteries have high energy density and are widely used in new energy electric vehicles and energy storage. However, lithium resources are limited and expensive, making it difficult for lithium-ion batteries to meet the growing demands of new energy electric vehicles and energy storage. Since sodium resources are abundant and their cost is much lower than that of lithium resources, and sodium and lithium have similar electrochemical properties, developing safe and high-performance sodium-ion batteries is the future direction.

[0003] O3-type layered oxide sodium-ion cathode materials have high discharge specific capacity. However, layered oxide sodium-ion cathode materials have poor air stability, high residual alkali, and are difficult to process when preparing batteries, which greatly limits the application of sodium-ion batteries. Therefore, improving the stability of sodium-ion cathode materials is crucial.

[0004] Patent CN114725357A discloses a method for reducing sodium ion content in cathode materials. This method involves mixing the cathode material with an acidic solution to reduce residual alkali. However, washing the cathode material with an acidic solution can damage the surface of the cathode material, cause the transition metal to dissolve, and destroy the structure of the cathode material. As a result, the performance degrades too quickly during cycling. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a sodium-ion cathode material with low residual alkali content and its preparation method. Research has shown that controlling the ratio of specific positions in the XRD crystal structure of the sodium-ion cathode material within a specified range can facilitate sodium ion extraction, effectively suppress irreversible phase transitions, and improve the material's structural stability. The preparation method provided by this invention uses two precursors of different particle sizes, sintered and mixed separately. By controlling sintering and coating conditions, an excellent crystal structure can be obtained. The sodium-ion battery obtained using this method possesses the specific XRD crystal structure of this invention, improving the surface stability of the sodium-ion cathode material, preventing side reactions with the electrolyte and the dissolution of metal ions, and resulting in a sodium-ion cathode material with even lower residual alkali content.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0007] A sodium-ion cathode material with low residual alkali content, its structure is Na x Ni y Fe z Cu a Mn b M 1-y-z-a-bO2, where 0.70≤x≤1.20, 0<y≤0.6, 0<z≤0.4, 0<a≤0.1, 0<b≤0.4, and y+z+a+b<1, and M is selected from one or more of Mg, Ca, Sr, Zr, Ti, W, and B.

[0008] Preferably, the positive electrode material is coated with aluminum;

[0009] Preferably, the positive electrode material is further coated with phosphate.

[0010] In the XRD crystal structure of the sodium-ion cathode material, the ratio of I(113) / I(018) is between 0.7 and 1.2, and the ratio of FWHM(113) / FWHM(018) is between 1.2 and 1.8; the ratio of I(006) / I(101) is between 0.6 and 1.3, and the ratio of FWHM(006) / FWHM(101) is between 1.0 and 1.5; the sum of peak intensities of impurity peaks between 38° and 39° is less than 0.2 compared to I(012); and there are no NiO impurity peaks between 40° and 45°.

[0011] During cycling, layered cathode materials in the O3 phase undergo a phase transition, transforming from the O3 phase to the irreversible P3 phase. Studies have shown that within specified ranges, the ratios I(113) / I(018), I(006) / I(101), FWHM(113) / FWHM(018), and FWHM(006) / FWHM(101) can facilitate sodium ion extraction, effectively suppressing the irreversible phase transition and improving the material's structural stability. When the ratio of the sum of the peak intensities of impurity peaks between 38° and 39° to I(102) is less than 0.2, it indicates that Cu elements are stable in the material without precipitation; the absence of impurity peaks between 40° and 45° indicates the absence of rock salt phase impurity peaks on the cathode material surface, further enhancing material stability.

[0012] The cathode material of the present invention, after being placed in water and stirred for 5 minutes, retains a spherical shape and does not dissociate; the main peaks of (003) and (104) in the XRD pattern remain intact and do not disappear.

[0013] In one specific implementation, the sodium-ion battery cathode material has a pH ≤ 12.3; residual NaOH (ethanol as solvent) on the surface ≤ 500 ppm; Na2CO3 ≤ 10000 ppm; H2O ≤ 200 ppm; and after the cathode material is exposed to an environment with 30% humidity for 4 hours, H2O ≤ 400 ppm.

[0014] This invention also provides a method for preparing a sodium-ion cathode material with low residual alkali content, comprising the following steps:

[0015] Step 1): Select two precursors of nickel-iron-copper-manganese with different particle sizes;

[0016] Step 2): Two precursors of different particle sizes, nickel-iron-copper-manganese, are mixed with a sodium source and an optional compound M in a certain proportion. The mixture is then sintered. The entire sintering process includes three steps: the first step is sintering at temperature T1 under an oxygen or compressed air atmosphere; the second step is sintering at a temperature T2; and the third step is sintering at a temperature T3 to obtain sodium cathode materials with two particle size matrices.

[0017] Step 3): The two types of sodium cathode materials obtained in Step 2) are added together with the Al compound into a high-speed mixer and thoroughly mixed. The mixture is then sintered at a certain temperature to obtain Al-coated sodium cathode materials.

[0018] Step 4): The two cathode materials obtained in Step 3 are mixed with phosphate and sintered at a certain temperature to obtain two sodium cathode materials with low residual alkali content coated with phosphate.

[0019] Step 5): Mix the two sodium cathode materials with different particle sizes at a certain mass ratio to obtain sodium cathode materials with low residual alkali content.

[0020] In a specific implementation, let the particle sizes of the two precursors with different particle sizes in step 1) be Y1 and Y2, respectively.

[0021] a) The D50 of Y1 is 2-7 μm, preferably 3-6 μm; the BET is 5-25 μm. 2 / g, preferably 10-20m 2 / g; Particle size distribution (D90-D10) / D50 is 0.4-1.0, preferably 0.5-0.9;

[0022] b) The D50 of Y2 is 8-18 μm, preferably 10-16 μm; the BET is 5-20 μm. 2 / g, preferably 8-18m 2 / g; Particle size distribution (D90-D10) / D50 is 0.1-0.6, preferably 0.2-0.5.

[0023] In one specific implementation, the structure of the nickel-iron-copper-manganese precursor is Ni y Fe z Cu a Mn b (OH)2, where 0 < y ≤ 0.6, 0 < z ≤ 0.4, 0 < a ≤ 0.1, and 0 < b ≤ 0.4.

[0024] In one specific implementation, the amount of sodium source added in step 2) is based on a molar ratio Na:Me = 0.7-1.2:1, where Me is the sum of the molar amounts of Ni, Fe, Cu, and Mn; more preferably, the sodium source is selected from any one or more of sodium carbonate, sodium hydroxide, sodium oxalate, or sodium acetate.

[0025] In one specific implementation, the compound containing M in step 2) is selected from one or more of Mg, Ca, Sr, Zr, Ti, W, and B; preferably, the amount of compound M incorporated is 0-1.0% of the total mass of nickel, iron, copper, and manganese, and preferably the amount of M incorporated is not 0.

[0026] In one specific implementation, the atmosphere in step 2) is compressed air or oxygen, the sintering temperature T1 is 600-900℃, the sintering time is 3-6h; the sintering temperature T2 is 800-1000℃, the sintering time is 8-15h; and the sintering temperature T3 is 400-700℃, the sintering time is 2-4h.

[0027] Preferably, the sintering temperature T2 is greater than T1.

[0028] In one specific implementation, in step 3), the aluminum compound is one or more of aluminum oxide, aluminum hydroxide, aluminum chloride, or aluminum nitrate; the Al coating amount is 0.05%-0.3% of the mass of the sodium-ion cathode material obtained in step 2); the sintering temperature is 300-700℃; and the sintering time is 5-10h.

[0029] In one specific implementation, step 4) uses either NaFePO4 or Na3V2(PO4)3 as the phosphate; the coating amount of the phosphate is 0.05%-0.5% of the mass of the Al-coated sodium cathode material obtained in step 3); the sintering temperature is 400-800℃; and the sintering time is 5-10h.

[0030] In one specific implementation, in step 5), the mass ratio of the sodium cathode material with low residual alkali content coated with phosphate prepared from the precursor with particle size Y2 to the sodium cathode material with low residual alkali content coated with phosphate prepared from the precursor with particle size Y1 is 2-5:1.

[0031] In one specific implementation, the slurry viscosity of the sodium-ion cathode material is ≤8000 mPa·s during the battery manufacturing process, and it is fluid; after standing for 24 hours, the slurry viscosity is ≤10000 mPa·s, and the slurry is fluid; in a half-cell at 2.0–4.0 V, the 0.2C discharge capacity is greater than 130 mAh / g, and the average voltage is greater than 3.0 V.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] This invention has found that: when the I(006) / I(101) and FWHM(006) / FWHM(101) ratios in the XRD crystal structure are within a suitable range, the sodium interlayer spacing is appropriate, which is conducive to the extraction of sodium ions and results in high capacity; when the I(113) / I(018) and FWHM(113) / FWHM(018) ratios are within a suitable range, irreversible phase transitions can be effectively suppressed during cycling, resulting in a more stable sodium-ion battery material structure and lower residual alkali content; this invention optimizes two different particle sizes The precursors are sintered with the sodium source separately. By adjusting the optimal sodium ratio and sintering temperature of precursors with different particle sizes, it is beneficial to obtain the specific crystal structure of the present invention. Through the co-doping of metal elements in the metal layer and sodium layer, as well as the coating of aluminum and phosphate, it is beneficial to obtain suitable I(006) / I(101) values ​​and FWHM(006) / FWHM(101) values, which improves the stability of the sodium layer, prevents side reactions with the electrolyte and dissolution of metal ions, and prepares a stable sodium ion cathode material with low residual alkali content.

[0034] The sodium ion cathode material of the present invention has high air stability, low residual alkali, excellent electrical properties, and can be processed into slurry at an ambient humidity of 30%. Attached Figure Description

[0035] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 of this invention after washing with water.

[0036] Figure 2 The image shows a SEM image of the cathode material prepared in Comparative Example 1 after washing.

[0037] Figure 3 This is the XRD pattern of the positive electrode material prepared in Example 1 of this invention after washing with water.

[0038] Figure 4 This is the XRD pattern of the cathode material prepared in Comparative Example 1 after washing with water.

[0039] Figure 5 This is a graph showing the moisture growth trend of the cathode materials prepared in Example 1 and Comparative Example 1 of this invention when exposed to a humidity of 30%. Detailed Implementation

[0040] The following embodiments will further illustrate the method provided by the present invention, but the present invention is not limited to the listed embodiments and should also include any other known modifications within the scope of the claims of the present invention.

[0041] Residual alkali: Equipment model: 905, Manufacturer: Metrohm, Switzerland; Method: GB / T 41704-2022

[0042] Moisture content: Equipment model: 851+860, manufacturer: Metrohm, Switzerland; Method: GB / T 6283-2008

[0043] XRD: Equipment Model: Aeris; Manufacturer: Malvern Panaco

[0044] A method for preparing a stable sodium-ion battery cathode material with low residual alkali content, the method comprising the following steps:

[0045] 1) Select two precursors of nickel-iron-copper-manganese with different particle sizes (Y1 and Y2);

[0046] 2) Step 2: Two precursors of different particle sizes of nickel, iron, copper and manganese are mixed with the compound of M and sodium source in a certain proportion. The mixture is sintered. The whole sintering process is divided into three steps: the first step is to sinter under an atmosphere and at a temperature of T1; the second step is to sinter at a temperature of T2; the third step is to sinter at a temperature of T3 to obtain sodium cathode materials with two different particle size matrices.

[0047] 3) Step 3: The two types of matrix sodium cathode materials obtained in step 2 are added together with the Al compound into a high-speed mixer and thoroughly mixed. The mixture is then sintered at a certain temperature to obtain Al-coated sodium cathode materials.

[0048] 4) Step 4: Add the two cathode materials obtained in step 3 to sodium phosphate (NaXPO4) and mix them thoroughly in a high-speed mixer. Then, sinter them at a certain temperature to obtain two stable sodium cathode materials with low residual alkali content coated with phosphate.

[0049] 5) Step 5: Mix the two sodium cathode materials with different particle sizes at a certain mass ratio to obtain the final sodium cathode material with low residual alkali content.

[0050] The present invention will be further explained and illustrated below through more specific embodiments, but these do not constitute any limitation.

[0051] Example 1

[0052] 1) Weigh 100g of Ni from Y1 0.23 Fe 0.33 Cu 0.10 Mn 0.34The (OH)₂ precursor, with a particle size D50 of 3.5 μm and a (D90-D10) / D50 ratio of 0.96, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1 in a ball mill. Then, 0.1% MgO (by mass of the precursor) and 0.6% CaCO₃ (by mass of the precursor) were added to the ball mill and mixed. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0053] 0.1% by weight of Al2O3 was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0054] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 1.

[0055] 2) Weigh 100g of Ni from Y2 0.23 Fe 0.33 Cu 0.10 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 10.5 μm and a (D90-D10) / D50 ratio of 0.42, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1. Additionally, 0.1% MgO and 0.6% CaCO₃ (by mass of the precursor) were added to a ball mill for mixing. The mixture was sintered at 800 °C for 240 min in air, then at 920 °C for 600 min, and finally at 600 °C for 180 min to obtain the doped cathode material.

[0056] 0.1% by weight of Al2O3 was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0057] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 2.

[0058] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 8:2, a stable cathode material with low residual alkali content is obtained.

[0059] 4) The physicochemical properties of the prepared cathode material are as follows: pH: 11.95; NaOH: 215 ppm; Na2CO3: 4783 ppm; H2O: 136 ppm; H2O after exposure to 30% humidity for 4 hours: 312 ppm; I(113) / I(018): 0.9; FWHM(113) / FWHM(018): 1.6; I(006) / I(101): 1.0; FWHM(006) / FWHM(101): 1.1; the sum of peak intensities of impurity peaks between 38° and 39° and I(012): 0.08. (The test method has been provided above.)

[0060] 5) Fabricate coin cells from the positive electrode material and test their performance. The slurry viscosity is 6100 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and electrical performance is tested using the Newwell coin cell testing system (name changed, coin cell testing equipment manufacturers are not unique) (charge and discharge voltages are 2.00~4.00V respectively).

[0061] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 145 mAh / g and a 0.2C first-time efficiency of 94.3%.

[0062] After the cathode material was placed in water and stirred for 5 minutes, its morphology remained spherical and there was no dissociation; the main peaks of (003) and (104) in the XRD pattern remained intact and did not disappear.

[0063] Comparative Example 1

[0064] 1) Weigh 100g of Ni from Y1 0.23 Fe 0.33 Cu 0.10 Mn 0.34 The (OH)₂ precursor had a particle size D50 of 3.5 μm and a (D90-D10) / D50 ratio of 0.96. Sodium carbonate and the precursor powder were mixed in a ball mill at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the cathode material.

[0065] 0.1% by weight of Al2O3 was added to the matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0066] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 1.

[0067] 2) Weigh 100g of Ni from Y2 0.23 Fe 0.33 Cu 0.10 Mn 0.34 The (OH)₂ precursor had a particle size D50 of 10.5 μm and a (D90-D10) / D50 ratio of 0.42. Sodium carbonate and the precursor powder were mixed in a ball mill at a ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1. The mixture was sintered at 800 °C for 240 min in air, then sintered at 920 °C for 600 min, and finally sintered at 600 °C for 180 min to obtain the cathode material.

[0068] 0.1% by weight of Al2O3 was added to the matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0069] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 2.

[0070] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 8:2, a cathode material with low residual alkali content is obtained.

[0071] 4) The physicochemical properties of the obtained cathode material are: pH: 12.65; NaOH: 783ppm; Na2CO3: 9346ppm; H2O: 421ppm; H2O after exposure to 30% humidity for 4 hours: 852ppm; I(113) / I(018): 0.6; FWHM(113) / FWHM(018): 1.9; I(006) / I(101): 0.5; FWHM(006) / FWHM(101): 1.7; the sum of peak intensities of impurity peaks between 38° and 39° and I(012): 0.21.

[0072] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 8300 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0073] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 137 mAh / g and a 0.2C first-time efficiency of 92.6%.

[0074] Example 2

[0075] 1) Weigh out 100 Y1 of Ni 0.27 Fe 0.33 Cu 0.06 Mn0.34 The (OH)₂ precursor, with a particle size D50 of 4.0 μm and a (D90-D10) / D50 ratio of 0.91, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 0.99:1. Doping amounts of 0.1% MgO and 0.8% CaCO₃ (based on the precursor mass) were added to a ball mill for mixing. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0076] 0.2% by weight of Al2O3 of the doped cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0077] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 1.

[0078] 2) Weigh 100g of Ni from Y2 0.27 Fe 0.33 Cu 0.06 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 11.0 μm and a (D90-D10) / D50 ratio of 0.47, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 0.99:1. Doping amounts of 0.1% MgO and 0.8% CaCO₃ (based on the precursor mass) were added to a ball mill for mixing. The mixture was sintered at 800℃ for 240 min in air, then at 920℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0079] 0.2% by weight of Al2O3 was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0080] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 2.

[0081] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 8:2, a cathode material with low residual alkali content is obtained.

[0082] 4) The physicochemical properties of the obtained cathode material are: pH: 12.07; NaOH: 287ppm; Na2CO3: 3283ppm; H2O: 187ppm; H2O after exposure to 30% humidity for 4 hours: 345ppm; I(113) / I(018): 1.05; FWHM(113) / FWHM(018): 1.47; I(006) / I(101): 0.92; FWHM(006) / FWHM(101): 1.18; the sum of peak intensities of the impurity peaks between 38° and 39° and I(012): 0.06.

[0083] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 6300 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0084] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 146 mAh / g and a 0.2C first-time efficiency of 94.6%.

[0085] Comparative Example 2

[0086] 1) Weigh 100g of Ni from Y1 0.27 Fe 0.33 Cu 0.06 Mn 0.34 The (OH)₂ precursor had a particle size D50 of 4.0 μm and a (D90-D10) / D50 ratio of 0.91. Sodium carbonate and the precursor powder were mixed in a ball mill at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 0.99:1. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain cathode material 1.

[0087] 2) Weigh 100g of Ni from Y2 0.27 Fe 0.33 Cu 0.06 Mn 0.34 The (OH)₂ precursor had a particle size D50 of 11.0 μm and a (D90-D10) / D50 ratio of 0.47. Sodium carbonate and the precursor powder were mixed in a ball mill at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 0.99:1. The mixture was sintered at 800 °C for 240 min in air, then sintered at 920 °C for 600 min, and finally sintered at 600 °C for 180 min to obtain cathode material 2.

[0088] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 8:2, a cathode material with low residual alkali content is obtained.

[0089] 4) The physicochemical properties of the obtained cathode material are: pH: 13.15; NaOH: 984ppm; Na2CO3: 8783ppm; H2O: 534ppm; H2O after exposure to 30% humidity for 4 hours: 975ppm; I(113) / I(018): 1.27; FWHM(113) / FWHM(018): 1.16; I(006) / I(101): 1.34; FWHM(006) / FWHM(101): 0.93; the sum of peak intensities of the impurity peaks between 38° and 39° and I(012): 0.23.

[0090] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 9400 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0091] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 132 mAh / g and a 0.2C first-time efficiency of 91.9%.

[0092] Example 3

[0093] 1) Weigh 100g of Ni with a particle size D50 of 3.0umY1. 0.23 Fe 0.33 Cu 0.10 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 3.0 μm and a (D90-D10) / D50 ratio of 0.93, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1. Doping amounts of 0.1% MgO, 0.2% ZrO₂, and 0.6% CaCO₃ (by precursor mass) were added to a ball mill. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0094] 0.1% by weight of Al2O3 was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0095] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 1.

[0096] 2) Weigh 100g of Ni from Y2 0.23 Fe 0.33Cu 0.10 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 11.5 μm and a (D90-D10) / D50 ratio of 0.44, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1. Doping amounts of 0.1% MgO, 0.2% ZrO₂, and 0.6% CaCO₃ (by precursor mass) were added to a ball mill. The mixture was sintered at 800 °C for 240 min in air, then at 920 °C for 600 min, and finally at 600 °C for 180 min to obtain the doped cathode material.

[0097] 0.1% by weight of Al2O3 of the doped cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0098] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 2.

[0099] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 8:2, a cathode material with low residual alkali content is obtained.

[0100] 4) The physicochemical properties of the obtained cathode material are: pH: 11.89; NaOH: 247ppm; Na2CO3: 4361ppm; H2O: 148ppm; H2O after exposure to 30% humidity for 4 hours: 300ppm; I(113) / I(018): 1.10; FWHM(113) / FWHM(018): 1.39; I(006) / I(101): 1.05; FWHM(006) / FWHM(101): 1.09; The sum of peak intensities of the impurity peaks between 38° and 39° and I(012): 0.07.

[0101] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 5900 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0102] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 143 mAh / g and a 0.2C first-time efficiency of 94.5%.

[0103] Comparative Example 3

[0104] 1) Weigh 100g of Ni from Y1 0.23 Fe0.33 Cu 0.10 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 3.0 μm and a (D90-D10) / D50 ratio of 0.93, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1. Doping amounts of 0.1% MgO, 0.2% ZrO₂, and 0.6% CaCO₃ (by precursor mass) were added to a ball mill. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0105] 0.1% by weight of Al2O3 was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material 1.

[0106] 2) Weigh 100g of Ni from Y2 0.23 Fe 0.33 Cu 0.10 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 11.5 μm and a (D90-D10) / D50 ratio of 0.44, was mixed with sodium carbonate and the precursor powder at a ratio of Na / (Ni+Fe+Cu+Mn) = 1.00:1, along with doping amounts of 0.1% MgO, 0.2% ZrO₂, and 0.6% CaCO₃ in a ball mill. The mixture was sintered at 800 °C for 240 min in air, then at 900 °C for 600 min, and finally at 600 °C for 180 min to obtain the doped cathode material.

[0107] 0.1% of the mass of Al2O3 of the cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material 2.

[0108] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 8:2, a cathode material with low residual alkali content is obtained.

[0109] 4) The physicochemical properties of the obtained cathode material are: pH: 12.37; NaOH: 421ppm; Na2CO3: 8545ppm; H2O: 214ppm; H2O after exposure to 30% humidity for 4h: 423ppm; I(113) / I(018): 1.36; FWHM(113) / FWHM(018): 1.12; I(006) / I(101): 1.42; FWHM(006) / FWHM(101): 0.89; the sum of peak intensities of the impurity peaks between 38° and 39° and I(012): 0.22.

[0110] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 7200 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0111] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 137 mAh / g and a 0.2C first-time efficiency of 93.2%.

[0112] Example 4

[0113] 1) Weigh 100g of Ni from Y1 0.27 Fe 0.33 Cu 0.06 Mn 0.34 The (OH)₂ precursor, with a particle size D50 of 5.0 μm and a (D90-D10) / D50 ratio of 0.89, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 0.99:1. Doping amounts of 0.1% MgO, 0.1% TiO₂, and 0.8% CaCO₃ (based on the precursor mass) were added to a ball mill. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0114] 0.1% by weight of Al2O3 of the doped cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0115] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 1.

[0116] 2) Weigh 100g of Ni from Y2 0.27 Fe 0.33 Cu 0.06 Mn 0.34The (OH)₂ precursor, with a particle size D50 of 12.0 μm and a (D90-D10) / D50 ratio of 0.43, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 0.99:1. Doping amounts of 0.1% MgO, 0.1% TiO₂, and 0.8% CaCO₃ (based on the precursor mass) were added to a ball mill. The mixture was sintered at 800℃ for 240 min in air, then at 920℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0117] 0.1% by weight of Al2O3 of the doped cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0118] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 2.

[0119] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 7:3, a cathode material with low residual alkali content is obtained.

[0120] 4) The physicochemical properties of the obtained cathode material are: pH: 11.98; NaOH: 263ppm; Na2CO3: 3176ppm; H2O: 170ppm; H2O after exposure to 30% humidity for 4 hours: 323ppm; I(113) / I(018): 1.01; FWHM(113) / FWHM(018): 1.38; I(006) / I(101): 0.87; FWHM(006) / FWHM(101): 1.23; the sum of peak intensities of impurity peaks between 38° and 39° and I(012): 0.05.

[0121] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 6100 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0122] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 144 mAh / g and a 0.2C first-time efficiency of 94.8%.

[0123] Example 5

[0124] 1) Weigh 100g of Ni from Y1 0.20 Fe 0.30 Cu 0.10 Mn0.40 The (OH)₂ precursor, with a particle size D50 of 3.5 μm and a (D90-D10) / D50 ratio of 0.90, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.02:1. Dopant amounts of 0.1% MgO, 0.1% TiO₂, and 0.6% CaCO₃ (based on precursor mass) were added to a ball mill for mixing. The mixture was sintered at 800℃ for 240 min in air, then at 900℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0125] 0.1% by weight of Al2O3 of the doped cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0126] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 1.

[0127] 2) Weigh 100g of Ni with a particle size D50 of 11.0um (Y2). 0.20 Fe 0.30 Cu 0.10 Mn 0.40 The (OH)₂ precursor, with a particle size D50 of 11.0 μm and a (D90-D10) / D50 ratio of 0.46, was mixed with sodium carbonate and precursor powder at a molar ratio of Na / (Ni+Fe+Cu+Mn) = 1.02:1. Doping amounts of 0.1% MgO, 0.1% TiO₂, and 0.6% CaCO₃ (based on the precursor mass) were added to a ball mill. The mixture was sintered at 800℃ for 240 min in air, then at 920℃ for 600 min, and finally at 600℃ for 180 min to obtain the doped cathode material.

[0128] 0.1% by weight of Al2O3 of the doped cathode material was added to the doped matrix and mixed in a ball mill. The mixture was then sintered at 600°C for 480 min in an air atmosphere to obtain Al-coated cathode material.

[0129] 0.2% NaFePO4 by mass of Al-coated cathode material was added to a ball mill and mixed with the Al-coated cathode material. The mixture was then sintered at 700°C for 360 min in an air atmosphere to obtain the final cathode material 2.

[0130] 3) After mixing cathode material 2 and cathode material 1 at a mass ratio of 7:3, a cathode material with low residual alkali content is obtained.

[0131] 4) The physicochemical properties of the obtained cathode material are: pH: 11.87; NaOH: 251ppm; Na2CO3: 4172ppm; H2O: 184ppm; H2O after exposure to 30% humidity for 4 hours: 300ppm; I(113) / I(018): 1.07; FWHM(113) / FWHM(018): 1.43; I(006) / I(101): 0.93; FWHM(006) / FWHM(101): 1.28; the sum of peak intensities of impurity peaks between 38° and 39° and I(012): 0.06.

[0132] 5) Fabricate coin cells using the positive electrode material and test their performance. The slurry viscosity is 6300 mPa·s; 2032 coin cells are assembled using sodium metal sheets as the negative electrode, and their electrical performance is tested using the Newwell coin cell testing system (charge and discharge voltages are 2.00–4.00 V).

[0133] The results show that the cathode material with low residual alkali content has a 0.2C discharge capacity of 142 mAh / g and a 0.2C first-time efficiency of 94.1%.

[0134] SEM images of Example 1 and Comparative Example 1 after washing are shown below. Figure 1 It can be seen that the morphology and structure of Example 1 are stable.

[0135] XRD patterns after water washing in Example 1 and Comparative Example 1 are as follows: Figure 2 It can be seen that the crystal structure of the cathode material in Example 1 is stable.

[0136] The H2O of the materials after placement in Example 1 and Comparative Example 1 is as follows: Figure 3 It can be seen that the structure of Example 1 is stable.

[0137] The 0.2C discharge capacity of Examples 1, 2, 3, 4, and 5 is shown in Table 1. The sodium-ion cathode material exhibits excellent electrical properties.

[0138] Table 1 shows the capacity of the embodiments within the charging voltage range of 4.4V to 4.75V.

[0139]

[0140]

[0141] Although the present invention has been described in detail through the preferred embodiments described above, it should be understood that the above description should not be considered as a limitation of the present invention. Those skilled in the art will understand that modifications or adjustments can be made to the present invention based on the teachings of this specification. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A sodium-ion cathode material with low residual alkali content, characterized in that, Its structure is Na x Ni y Fe z Cu a Mn b M 1-y-z-a- b O2, where 0.70≤x≤1.20, 0<y≤0.6, 0<z≤0.4, 0<a≤0.1, 0<b≤0.4, and y+z+a+b<1, M is selected from one or more of Mg, Ca, Sr, Zr, Ti, W, and B; In the XRD crystal structure of the sodium ion cathode material, the ratio of I(113) / I(018) is between 0.7 and 1.2, and the ratio of FWHM(113) / FWHM(018) is between 1.2 and 1.8; the ratio of I(006) / I(101) is between 0.6 and 1.3, and the ratio of FWHM(006) / FWHM(101) is between 1.0 and 1.

5. The positive electrode material is coated with aluminum; the positive electrode material is also coated with phosphate.

2. The cathode material according to claim 1, characterized in that, 38 。 -39 。 The ratio of the sum of the peak intensities of the interstitial peaks to I(012) is less than 0.2; in the range of 40-45... 。 There are no NiO impurity peaks between them.

3. A method for preparing the sodium-ion cathode material according to any one of claims 1-2, characterized in that, Includes the following steps: Step 1): Select two precursors of nickel-iron-copper-manganese with different particle sizes; Step 2): Two precursors of different particle sizes, nickel-iron-copper-manganese, are mixed with a sodium source and a compound of choice M, respectively. The mixture is then sintered in three steps: the first step is sintering at temperature T1 under an oxygen or compressed air atmosphere; the second step is sintering at a temperature T2; and the third step is sintering at a temperature T3 to obtain sodium cathode materials with two particle size matrices. Step 3): The two types of sodium cathode materials with different substrates obtained in Step 2) are thoroughly mixed with Al compounds and sintered to obtain Al-coated sodium cathode materials; Step 4): Mix the two cathode materials obtained in Step 3 with phosphates respectively, and then sinter them to obtain two sodium cathode materials with low residual alkali content coated with phosphates. Step 5): Mix the two sodium cathode materials with different particle sizes obtained in Step 4) evenly to obtain a sodium cathode material with low residual alkali content.

4. The preparation method according to claim 3, characterized in that, wherein... In step 1), the particle sizes of the two precursors with different particle sizes are Y1 and Y2, respectively. a) D50 of Y1 is 2-7 μm; BET is 5-25 μm. 2 / g; Particle size distribution (D90-D10) / D50 is 0.4-1.0; b) The D50 of Y2 is 8-18 μm; the BET is 5-20 μm. 2 / g; Particle size distribution (D90-D10) / D50 is 0.1-0.

6.

5. The preparation method according to claim 4, characterized in that, Let the particle sizes of the two precursors with different particle sizes in step 1) be Y1 and Y2, then a) The D50 of Y1 is 3-6 μm; the BET is 10-20 μm. 2 / g; Particle size distribution (D90-D10) / D50 is 0.5-0.9; b) The D50 of Y2 is 10-16 μm; the BET is 8-18 μm. 2 / g; Particle size distribution (D90-D10) / D50 is 0.2-0.

5.

6. The preparation method according to claim 4 or 5, characterized in that, The precursor of nickel-iron-copper-manganese has the structural formula Ni y Fe z Cu a Mn b (OH)2, where 0 < y ≤ 0.6, 0 < z ≤ 0.4, 0 < a ≤ 0.1, and 0 < b ≤ 0.

4.

7. The preparation method according to claim 3, characterized in that, The amount of sodium source added in step 2) is calculated based on a molar ratio of Na:Me = 0.7-1.2:1, where Me is the sum of the molar amounts of Ni, Fe, Cu, and Mn.

8. The preparation method according to claim 3, characterized in that, The sodium source is selected from one or more of sodium carbonate, sodium hydroxide, sodium oxalate, or sodium acetate.

9. The preparation method according to claim 3, characterized in that, In step 2), the compound containing M is selected from one or more of Mg, Ca, Sr, Zr, Ti, W, and B.

10. The preparation method according to claim 3, characterized in that, The amount of M added is 0-1.0% of the total mass of nickel, iron, copper and manganese metals, and the amount of M added is not 0.

11. The preparation method according to claim 3, characterized in that, In step 2), the atmosphere is compressed air or oxygen, the sintering temperature T1 is 600-900℃, the sintering time is 3-6h; the sintering temperature T2 is 800-1000℃, the sintering time is 8-15h; the sintering temperature T3 is 400-700℃, the sintering time is 2-4h.

12. The preparation method according to claim 3, characterized in that, In step 2), the sintering temperature T2 is greater than T1.

13. The preparation method according to claim 3, characterized in that, Step 3) The aluminum compound is one or more of aluminum oxide, aluminum hydroxide, aluminum chloride or aluminum nitrate; the Al coating amount is 0.05%-0.3% of the mass of the sodium electrode material obtained in Step 2); the sintering temperature is 300-700℃; and the sintering time is 5-10h.

14. The preparation method according to claim 3, characterized in that, Step 4) The phosphate is one or more of NaFePO4 and Na3V2(PO4)3; the coating amount of the phosphate is 0.05%-0.5% of the mass of the Al-coated sodium cathode material obtained in Step 3); the sintering temperature is 400-800℃; and the sintering time is 5-10h.

15. The preparation method according to claim 3, characterized in that, In step 5), the mass ratio of the sodium cathode material with low residual alkali content coated with phosphate prepared from the precursor with particle size Y2 to the sodium cathode material with low residual alkali content coated with phosphate prepared from the precursor with particle size Y1 is 2-5:1.

Citation Information

Patent Citations

  • Sodium-containing oxide positive electrode material, preparation method and application thereof, positive plate and application thereof

    CN114843498A

  • Ultrahigh-nickel polycrystalline nickel-aluminum-magnesium lithium zirconate positive electrode material as well as preparation method and application thereof

    CN114914440A